Characterization of a Novel Pyridinium Bromide Surface Confined Ionic Liquid Stationary Phase for High Performance Liquid Chromatography under Normal Phase Conditions via Linear Solvation Energy Relationships - Van Meter, D. S. (2008)
Utilizing Linear Solvation Free Energy Relationship methodology, a novel pyridinium bromide surface confined ionic liquid (SCIL) stationary phase was characterized under normal phase High Performance Liquid Chromatographic conditions. A limited set of neutral aromatic probe solutes were utilized to rapidly assess the utility of the LSER model, using mobile phases of hexane modified with 2-propanol. The excellent correlation of the global fit across the mobile phase composition range used in this study for the experimental and calculated retention values (R(2) = 0.994) indicates that the LSER model is an appropriate model of characterizing this polar bonded phase under normal phase conditions. For a limited subset of compounds, retention on the pyridinium bromide SCIL stationary phase is more highly correlated with that obtained on a cyano column than on a diol column under NP conditions.